Analisis Kesiapsiagaan Pendaki melalui Rekam Jejak Pengetahuan Pertolongan Pertama pada Kondisi Hipotermia Akut di Gunung - David Prasetya Anwar; Sahri (Pendidikan Kepelatihan Olahraga FKIP Universitas Riau, 2025)
Mountain climbing is one of the most popular forms of recreational sports, especially among young people who enjoy nature-based challenges. However, this activity carries several risks, one of which is acute hypothermia sudden and dangerous drop in body temperature that can threaten the safety of climbers, particularly those lacking sufficient knowledge and preparation. Hypothermia often occurs among novice climbers due to limited education and lack of experience in handling emergency conditions. This study aims to explore climbers’ knowledge of first aid for acute hypothermia, their level of preparedness, their responses during incidents, and the role of education and climbing experience in shaping their readiness. This research employs a qualitative approach with a field study method. The study involed six climbers, one basecamp manager, one SAR team member, and one Perhutani officer on Mount Andong via the Sawit route. Data were collected through observation, in-depth interviews, and documentation. Data validity was tested through triangulation and persistent field observation. The findings indicate that most informants understand the definition and symptoms of hypothermia and have taken preventive measures such as carrying warm clothing and planning their hiking time. For treatment, they commonly use passive warming methods such as sleeping bags, emergency blankets, and warm food or drinks. However, education provided by basecamp staff remains limited. These findings highlight the importance of on-site education and first aid simulations as essential forms of preparedness prior to hiking.